Integrasi Sosial Waria Dalam Kehidupan Bermasyarakat - Noorwidayati, Rr. Endah; Wibowo, Arif (UI Scholars Hub, 2016)
This research to study about the social integration of transgender in society This research was located in East Jakarta area. The method used for this research is qualitative method, which focusing on transgender and its influenced factors in the social integration process into society. The result shows its social integration process for transgender has not done well, through the following influenced factors social distance either it is objectively or subjectively; prejudice and discriminative; commmunity sanctions; group’s heterogeneity; geographical mobility; and transgender’s duration to stay in an area.